Identification of stable QTLs for seed oil content by combined linkage and association mapping in Brassica napus. (November 2016) - Sun, Fengming; Liu, Jing; Hua, Wei; Sun, Xingchao; Wang, Xinfa; Wang, Hanzhong
Highlights: Total 40 QTLs and 29 associations of seed oil content were detected by Linkage and association mapping, respectively. We identified 7 stable QTLs that were reproduced by different environments, populations and two mapping methods. Allele-specific PCR primers were designed for 7 stable QTLs. Abstract: Seed oil content is an important agricultural trait in rapeseed breeding. Although numerous quantitative trait locus (QTL) have been identified, most of them cannot be applied in practical breeding mainly due to environmental instability or large confidence intervals. The purpose of this study was to identify and validate high quality and more stable QTLs by combining linkage mapping and genome-wide association study (GWAS). For linkage mapping, we constructed two F2 populations from crosses of high-oil content (∼50%) lines 6F313 and 61616 with a low-oil content (∼40%) line 51070. Two high density linkage maps spanned 1987 cM (1659 bins) and 1856 cM (1746 bins), respectively. For GWAS, we developed more than 34, 000 high-quality SNP markers based on 227 accessions. Finally, 40 QTLs and 29 associations were established by linkage and association mapping in different environments. After merging the results, 32 consensus QTLs were obtained and 7 of them were identified by both mapping methods. Seven overlapping QTLs covered an average confidence interval of 183 kb and explained the phenotypic variation of 10.23 to 24.45%. We further developed allele-specific PCR primers to identify each of the seven QTLs. These stable QTLs should be useful in gene cloning and practical breeding application.